The Use of Statistical Methods in Croatian Enterprises During the Early Stages of COVID-19 - Berislav Žmuk (Naše gospodarstvo/Our economy, 2022)
The appropriate application of statistical methods in enterprises should have an important role in business decision-making processes. However, Croatian enterprises still tend to have certain resistance to statistical methods. The new challenges introduced by the COVID-19 pandemic emphasised the importance of conducting statistical analyses as support for making business decisions. In order to investigate the situation and attitudes towards the use of statistical methods, primary research was conducted in the form of a web survey on a sample of 768 Croatian enterprises, of which 40% use statistical methods in their business. The research revealed the level of statistical methods use in Croatian enterprises, demonstrated which statistical methods Croatian enterprises prefer, and defined who is most responsible for their use. Furthermore, the reasons for the use of statistical methods and the major obstacles to the use of more intensive statistical methods were also investigated. The results are described and discussed on an overall level and by considering the size of the enterprises.